Improving the delivery of medical education in rural medical colleges - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2021)
It is a fact that in most of the rural settings, especially in low- and middle-income nations, the access to health care services and facilities is quite difficult. The primary reason for origin of this problem lies in the fact that a major proportion of medical professionals are not willing to serve in rural areas. This is in turn can be linked with the obvious geographical disparity in distribution of medical colleges in both rural and urban settings, with most of them being present in urban locations. In order to accomplish the vision to create a cadre of competent medical professionals, who are fit to work in the capacity of a primary health care physician, it is an indispensable requirement to sensitize and give adequate number of learning experiences pertaining to rural medical education. The process of planning and execution of rural medical education needs careful and systematic consideration, otherwise we will find ourselves short in achieving the intended learning outcomes. To conclude, rural medical education is an important aspect of the medical training. It is high time that all the stakeholders join their hands and work together to improve the competence level of medical students and play our part in the making of a community health physician.